Slovenský internetový trh a populácia - Pizano, Veronika (Communication Today, 2025)
The paper deals with Slovak Internet market, its history and growth, online advertising and its revenues and the Internet population. It is the methods of its research that are important for the Internet population. The article describes different ways how to measure and analyse the Internet users and their socio-demographic attributes. The last chapter characterizes the Slovak Internet population.